Pemberdayaan Perempuan Melalui Pendirian Kelompok Usaha Serai Pitay Berbasis Socialpreneur Guna Meningkatkan Kesejahteraan Masyarakat Kupang NTT - Arian Agung Prasetiyawan (Transformatif : Jurnal Pengabdian Masyarakat, 2020)
KKN Nusantara 3T (Disadvantaged, Foremost, and Outermost) is the implementation of the Collective Labor Agreement between the Directorate General of Islamic Education of the Ministry of Religion and the Directorate General of Disadvantaged Areas of the Ministry of Villages Development of Disadvantaged Areas and Transmigration concerning Collaboration in the Development of a Higher Education Model Building a Village through Community Service which is signed August 7, 2019. The location of the implementation of the Community Service Program is classified into 2 Zones: the East Nusa Tenggara Province Zone with the theme "Peace Building" and the Maluku Province Zone with the theme "Trauma Healing". The method used is the ABCD (Asset Based Community driven Development) approach. The dedication carried out by the 3 Kupang Zone groups "Empowering Women through the Establishment of a Socialpreneur-Based Serai Pitay Business Group to Improve Welfare in Pitay Village, Sulamu District, Kupang, East Nusa Tenggara". In accordance with the analytical knife used, namely the ABCD (Asset Based Community driven Development) approach method, the program has gone through a series of stages starting from identifying natural resource assets in the form of abundant lemongrass plants, socialization and demonstration of making, FGD, formation of lemongrass business groups, making SOPs, assisting group management, and launching Serai Pitay Juice as a typical product of Pitay Village. The hope is that the group will continue to produce and develop products even though the KKN Nusantara 3T is over. In addition, we hope that women's empowerment and community welfare development in Pitay Village, Sulamu District can be realized.